2019
DOI: 10.1017/qua.2019.68
|View full text |Cite
|
Sign up to set email alerts
|

Tectonism and volcanism enhanced by deglaciation events in southern Iceland

Abstract: Southern Iceland is one of the main outlets of the Icelandic ice sheet and is subject to seismicity of both tectonic and volcanic origins along the South Iceland Seismic Zone (SISZ). A sedimentary complex spanning Marine Isotopic Stage 6 (MIS 6) to the present includes evidence of both activities. It includes a continuous sedimentary record since the Eemian interglacial period, controlled by a rapid deglaciation, followed by two marine glacioisostasy-forced transgressions, separated by a regression phase conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 174 publications
(287 reference statements)
0
3
0
Order By: Relevance
“…Thinning of ice overlying subglacial magma systems -such as those beneath the West Antarctic Ice Sheet 225 , Iceland 226 and Chile 227 -could stimulate volcanic activity [228][229][230] , resulting in more numerous and active lakes.…”
Section: Future Evolution Of Subglacial Lakesmentioning
confidence: 99%
“…Thinning of ice overlying subglacial magma systems -such as those beneath the West Antarctic Ice Sheet 225 , Iceland 226 and Chile 227 -could stimulate volcanic activity [228][229][230] , resulting in more numerous and active lakes.…”
Section: Future Evolution Of Subglacial Lakesmentioning
confidence: 99%
“…This hypothesis is supported by the elevated number of tephra deposits identified in Iceland records (Maclennan et al, 2002) and in Greenland during the deglacial period mostly of Icelandic origin, a few from Japanese and unknow origins (Bourne et al, 2016;Zielinski et al, 1997;Mortensen et al, 2005;Gronvold et al, 1995). Van Vliet-Lanoe et al (2020) found that the enhanced volcanic events are most likely related to stress unlocking during deglaciation events, which the occurrence of volcanism in Iceland is related to rifting events at the melting margin of the ice sheet. In the period of 14.6-13.1 ka in Southeast Alaska, the enhanced volcanic activity from the Mount Edgecumbe Volcanic Field has also been observed by Praetorius et al (2016).…”
Section: Long-term Volcanic Eruption Variabilitymentioning
confidence: 85%
“…origin, a few from Japanese and unknow origins (Bourne et al, 2016;Zielinski et al, 1997;Mortensen et al, 2005;Gronvold et al, 1995). Van Vliet-Lanoe et al (2020) found that the enhanced volcanic events are most likely related to stress unlocking during deglaciation events, which the occurrence of volcanism in Iceland is related to rifting events at the melting margin of the ice sheet. In the period of 14.6-13.1 ka in Southeast Alaska, the enhanced volcanic activity from the Mount Edgecumbe Volcanic Field has also been observed by Praetorius et al (2016).…”
Section: Long-term Volcanic Eruption Variabilitymentioning
confidence: 99%